Analysing the Smart Loaded Traffic Square System for Emergency Vehicles via the Use of a Deep Learning Model - Pahadiya, Bharat; Ranawat , Rekha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the realm of urban traffic management, particularly within densely populated traffic squares, ensuring the swift and unimpeded passage of emergency vehicles (EVs) presents a significant challenge. This study introduces a comprehensive Smart Loaded Traffic Square System (SLTSS) that leverages advanced deep learning models to optimize traffic flow for EVs amidst heavy congestion. Through an empirical analysis encompassing various convolutional neural network architectures, including AlexNet, VGG16, VGG19, ResNet 50, ResNet 101, and a proposed custom ResNet152 model, this paper evaluates the effectiveness of these models in classifying EVs from other vehicles within a traffic square setting. The methodology adopted for this study involves a step-wise approach, starting with data cleaning to ensure high-quality, noise-free images for model training. Following segmentation and feature extraction processes, each model was trained and tested on a dataset comprising images of diverse vehicles within urban traffic scenarios. The performance of each model was meticulously assessed based on accuracy, precision, recall, and F1-score metrics, providing a holistic view of their classification capabilities. Results from this study underscore the pronounced impact of model complexity on classification performance. The foundational AlexNet model established a baseline with an accuracy of 85%, precision of 83%, and an F1-score of 82.5%. Subsequent models exhibited incremental improvements, with VGG16 and VGG19 models reaching accuracies up to 90% and 89%, respectively. However, it was the ResNet series that demonstrated significant advancements, with ResNet 50 achieving a 92% accuracy, ResNet 101 further elevating this to 93%, and the proposed ResNet152 model topping the charts with a remarkable 94% accuracy, alongside commensurate improvements in precision, recall, and F1-scores. The comparative analysis vividly illustrates the correlation between the depth and sophistication of the neural network architecture and its ability to accurately classify EVs in complex urban traffic scenarios. The proposed ResNet152 model, in particular, showcased superior performance with a 94% precision, 95% recall, and a 94% F1-score, underlining the potential of deep architectures in enhancing the operational efficiency of emergency responses within loaded traffic environments.